Pengaruh Transformasi Ekonomi dari Sektor Pertanian ke Sektor Industri terhadap Pertumbuhan Ekonomi di Indonesia - Abdullah , Abdulrahman Taresh; Wasil, Mohammad (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
The purpose of this research is the research and development of the industrial sector'seconomy to the agricultural sector, as well as the influence of agricultural and industrial sectorson economic growth in Indonesia. The data used is time series data, 1960-2015. The method used in this research is Vector Error Correction Model (VECM). From the estimation results, it is concluded that the economic growth rate and the industrial sector negatively affect the agricultural sector, it can be said that the increasing economic growth achieved in Indonesia has increased the industrial sector and lower the agricultural sector. While the results of research that the agricultural sector negatively affect the economic growth while the industrial sector positively affects economic growth, in the sense that the agricultural sector has a bad contribution in economic growth in Indonesia.